AB0583 Revisiting Clinical Differences between Hipersensitivity Vasculitis and Henoch-SchÖNlein Purpura in Adults from A Defined Population. (10th June 2014) - Loricera, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; Santos-Gόmez, M.; Mata, C.; Martín, L.; Άlvarez, L.; González-Vela, M.C.; Rueda-Gotor, J.; González-Lόpez, M.A.; Armesto, S.; Peirό, E.; et al.
Abstract : Background: Hypersensitivity vasculitis (HV) and Henoch-Schönlein purpura (HSP) are the most common entities included within the category of cutaneous vasculitis (CV). Palpable purpura and histological changes characterized by the presence of leukocytoclastic vasculitis are common in both conditions. Because of that, considerable overlap between them is often seen. It is especially true when the CV occurs in adults. Objectives: Our aim was to assess the main clinical differences between HV and HSP in a wide and unselected series of adults with CV from a defined population. Methods: We reviewed the clinical records of 297 consecutive adults (age>20years) seen at a single center between January 1975 and December 2012 that were classified as having HSP or HV according to the criteria proposed by Michel et al. 1 . Results: Based on the inclusion criteria 102 adult patients (71 men/31 women) were classified as HSP and 195 (104 men/91 women) as HV. The mean age was similar in both groups (55.8±16.5 years in HSP and 56.8±18.3 years in HV). Precipitating events, usually an upper respiratory tract infection and/or drug intake, were more frequently observed in HV. Both at the beginning of the disease and when the CV was established clinical manifestations were more frequent in patients with HSP than in those with HV. It was the case for gastrointestinal (57.4% vs. 6.8%; p<0.001), joint (51.5% vs. 36.6%; p=0.01) and renal involvement (86.3% vs. 18.3%; p<0.001). Corticosteroid (56.7% vs. 22%; p<0.001) and cytotoxic drug (19.4% vs. 3.2%; p<0.001) use was also more common in patients with HSP. After a median follow-up of 15.5 (interquartile range- IQR; 3-37) months in HSP and 4 (IQR; 2-12) months in HV, the outcome was better in HV than in HSP. In this regard, complete recovery (72.6% vs. 85.4%; p=0.01) was more commonly observed in HV while residual renal involvement (15.3% vs. 4.2%; p<0.001) was more common in HSP. The disease relapsed in 35.3% of patients with HSP and in 24.4% with HV (p=0.07). Conclusions: Our results confirm the claim that these two diseases presenting with similar cutaneous involvement are certainly two separate entities with greater systemic involvement and less favorable outcome in HSP. References: Michel BA, Hunder GG, Bloch DA, Calabrese LH. Hypersensitivity vasculitis and Henoch-Schönlein purpura: a comparison between the two disorders. J Rheumatol. 1992; 19: 721-728. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3002